Isotomurus graminis Fjellberg (Collembola: Isotomidae) new for Iran, key to Iranian species in genus with comment on the validity of photographic records - Mayvan, Mahmood Mehrafrooz; Greenslade, Penelope (Zootaxa, 2020)
As part of a comparison of the collembolan fauna in soil of forest, grasslands and broadacre agriculture in north east Iran, several pale green specimens were found that complied with all characters of Isotomurus prasinus (Reuter, 1891) and keyed out as such in Potapov (2001) except that the body covering consisted of smooth mesochaetae and not ciliated chaetae as are present in prasinus according to Potapov (2001). On a more extensive examination of the recent literature, it was clear that the Iranian specimens belonged to the species Isotomurus graminis Fjellberg, 2007 described six years later. In his description, Fjellberg (2007) notes that some specimens of the new species could have previously been identified as I. prasinus in spite of having a different chaetotaxic covering. He also notes that, in a number of characters, it is identical with Isotomurus unifasciatus (Börner, 1901) but the colour differentiates them as this latter species usually has a broad, pigmented, longitudinal dorsal stripe.